Crowding In or Crowding Out? A Classical-Harrodian Perspective - Jamee K. Moudud (Levy Economics Institute of Bard College, 2000)
This paper investigates the effects of budget deficits within a classical-Harrodian framework in a closed economy. In this framework, growth and cycles are endogenous, underutilized capacity is a recurrent phenomenon, capacity utilization fluctuates around the normal level in the long run, and unemployment is persistent. Give the normal rate of profit, the key determinant of growth is the social savings rate. Along the warranted path when growth is balanced and is financed via retained earnings and equity, the social savings rate can be shown to be equal to the flow of business and household savings less the money and government bond holdings of the aggregate private sector–that is, it equals the flow of investable surplus available to firms to finance investment. An increase in the budget deficit always raises short-run output growth, although the stimulus is slowed down by the accumulation of debt by firms. However, with a fixed private savings rate, an increase in the deficit lowers the warranted path. If raising the warranted path is desired, appropriate policies that would raise the social saaving rate would have to be implemented. As in Harrod, whether crowding out is harmful depends on the rate of warranted growth relative to the natural growth rate.
Keywords: 330